Productive Failure to Promote Deeper Self-Directed Learning in Coding and Robotics Education - van Zyl, Sukie; Havenga, Marietjie; Avrakotos-King, Fotiene (Education sciences, 2025)
In a world characterized by unpredictable change, students in Computer Science education must be deeper self-directed learners who can take ownership of their learning and transfer knowledge and skills to new contexts. This article reports on how productive failure was incorporated into an introductory coding and robotics course to enhance deeper self-directed learning. The population was 42 fourth-year pre-service teachers from two different campuses of a South African University. All students were invited to participate in the research, and 37 students consented to participate. A basic interpretative qualitative research design was followed. Guided self-reflection documents were used as data-gathering methods, and data were analyzed by applying thematic data analysis. The research concluded that productive failure, incorporated with cooperative pair programming and self-reflection, in introductory coding and robotics education, shows promising results for developing deeper self-directed learning. Furthermore, it is suggested that solvable problems should initially be introduced, because the new coding and robotics environment already contributes to the complexity of tasks. It was secondly concluded that participants’ self-reflections deepened after engaging with unsolvable problems. Follow-up research is required to determine if the transfer of knowledge and skills to new contexts occurred.